Alcohol consumption and suicide risk in medical internship: A Peruvian multicentric study - Toro Huamanchumo, Carlos J. (2019)
Introduction and Aim: Suicide and harmful alcohol consumption are major health problems, especially in medical students. This study aimed to evaluate the association between risk for alcohol abuse and suicide risk in medical interns of Peruvian hospitals. Design and Methods: We conducted a multicentre cross-sectional study in medical interns from 18 Peruvian hospitals. We measured suicide risk, risk for alcohol abuse, depression and self-esteem using the Plutchik Suicide Risk Scale, CAGE, Zung Self-Rating Depression Scale and Rosenberg Self-Esteem Scale, respectively. We used χ2 and Student t-tests for descriptive analysis. To evaluate the association between risk for alcohol abuse and suicide risk we generated crude and adjusted Poisson regression models with robust variance and estimated prevalence ratios with 95% confidence intervals. Results: We surveyed 433 medical interns. The prevalence of suicide risk and risk for alcohol abuse was 19.6% and 27.5%, respectively. We found significant differences in suicide risk according to age (P < 0.001), region of origin (P = 0.002), with whom the participant lived (P < 0.001), university of origin (P = 0.040), type of hospital (P = 0.042), family history of attempted suicide (P = 0.043), self-esteem level (P < 0.001) and alcohol consumption (P < 0.001). In the adjusted model, age (PRa: 1.11, 95% confidence interval 1.05–1.17) and risk for alcohol abuse (PRa: 7.60, 95% confidence interval 4.46–12, 96) were associated with suicide risk. Discussion and Conclusions: Two out of 10 medical interns had a positive screening for suicide risk. Age and especially risk for alcohol abuse were the associated variables. © 2019 Australasian Professional Society on Alcohol and other Drugs